Commissioning eBook Impact Study: Report of Preliminary Findings from Phase 2 of the Evaluation of the Care Services Improvement Partnership (CSIP) - Tracey Maegusuku-Hewett (King's College London, 2008)
This summary presents key findings from the second phase of the evaluation of the Care Services Improvement Partnership (CSIP). Phase Two was carried out by researchers from King’s College London and the University of Swansea between December 2007 and February 2008. This study was commissioned by the Department of Health and comprised: (1) a knowledge review of the evidence base underpinning the care commissioning tools and guidance produced by CSIP and; (2) qualitative interviews with 25 commissioners working in local councils and Primary Care Trusts (PCTs). The overall aim was to explore how CSIP’s Commissioning Programme supports change across delivery agencies, focussing on one product in particular, the ‘Commissioning eBook’. The ‘Commissioning eBook’ is described as a resource to improve commissioning of community services and it is expected that commissioners will shape and contribute to it.